Peningkatan Literasi Digital Guru Guna Mengatasi Permasalahan Pembelajaran di Era Pandemi Covid-19 - Krida Singgih Kuncoro; S Sukiyanto; Muhammad Irfan; Ayu Fitri Amalia; Widowati Pusporini; Astuti Wijayanti; Sri Adi Widodo (Abdi Wiralodra : Jurnal Pengabdian Kepada Masyarakat, 2022)
The Covid-19 pandemic is one of the great catalysts that spurs transformation in the world of education. This encourages the importance of understanding teacher digital literacy in responding to educational transformation during the Covid-19 pandemic. The purpose of this Community Service (PkM) is to provide information and increase teacher knowledge of digital literacy during learning during the Covid-19 pandemic. The PkM targets are teachers in the provinces of West Java, Central Java, East Java, and DIY. The activity carried out was to provide education about the importance of digital literacy in responding to the transformation of education during the Covid-19 pandemic. The stages of this activity consist of 1) planning stage; 2) preparation stage, 3) implementation stage, and 4) evaluation stage. Before and after the activity, the PkM team provided a digital literacy questionnaire. The results of the PkM activity showed a significant increase in understanding of digital literacy, which was 21.3%.